SHOULD THE AREA BE MINED? THE PRECAUTIONARY PRINCIPLE AND THE ENVIRONMENTAL IMPACTS ON DEEP-SEA MINING A ÁREA DEVERIA SER MINERADA? O PRINCÍPIO DA PRECAUÇÃO E OS IMPACTOS AMBIENTAIS DA MINERAÇÃO EM FUNDOS MARINHOS - Moreira, Felipe Kern; Teixeira, Felipe de Macedo (Caderno de Relações Internacionais, 2020)
The purpose of this paper is to analyze the role of the precautionary principle in the regulations of seabed exploitation activities. In order to do this, it relates the current Mining Code with the events that served as the basis for the Code negotiation. The methodology applied in this research is predominantly qualitative and of the document analysis procedure. The documents examined are the rules and jurisdictional decisions emanated from the International Seabed Authority. In summary, this article analyzes the adoption of the precautionary principle in recent normative and decisional constructions regarding mining activities and environmental impacts in the deep seabed. In conclusion, it is pointed to the construction of a normative arrangement of jurisdictional consolidation of the precautionary principle in the exploration activities of the deep seabed. Moreover, given the uncertain nature of the consequences that mining in the deep seabed will bring, the adoption of the principle arises to ensure the reduction of environmental impacts.